2020
DOI: 10.1016/j.nimb.2019.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Castanea sativa shells and fruits: Compositional analysis by proton induced X-ray emission

Abstract: Chestnut fruits, from Castanea sativa Miller species, have been previously characterized mainly to study the nutritional and biochemical parameters, with mineral contents receiving less attention from the researchers, although these minerals are essential for several mechanisms in human body. In this study, a detailed elemental compositional analysis was performed using Proton Induced X-ray Emission (PIXE) to characterize two varieties of Castanea sativa Miller chestnuts (Longal and Judia). This study comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Results published in previous studies for As [34][35][36][37][38], Cd [36,37,[44][45][46][47], Pb [18,[35][36][37][44][45][46][47][48]54], and Zn [17,18,34,35,45,47,54,[57][58][59][60][61] are comparable to the findings from the present study. Our results are also in line with previous research carried out on samples of fruits and vegetables from Romania [16,49,50] and Moldavia [38].…”
Section: Reduce Heavy Metals In Fruits and Vegetables By Soaking With...supporting
confidence: 91%
“…Results published in previous studies for As [34][35][36][37][38], Cd [36,37,[44][45][46][47], Pb [18,[35][36][37][44][45][46][47][48]54], and Zn [17,18,34,35,45,47,54,[57][58][59][60][61] are comparable to the findings from the present study. Our results are also in line with previous research carried out on samples of fruits and vegetables from Romania [16,49,50] and Moldavia [38].…”
Section: Reduce Heavy Metals In Fruits and Vegetables By Soaking With...supporting
confidence: 91%
“…The available methods, such as high-performance liquid chromatography, high-performance liquid chromatography-tandem mass spectrometry, ultra-high-pressure liquid chromatography-quadrupole time-of-flight tandem mass spectrometry, atomic absorption spectrophotometry, , flame atomic absorption spectrometry, , X-ray fluorescence and emission quadrupole, , and inductively coupled plasma mass spectrometry for the detection of copper/iron have limitations of time-consuming and complicated procedures and requirement of sophisticated analytical instruments with a skilled analyst. Therefore, the fluorescence-based method has gained significant interest among analytical chemists to develop fluorescence chemosensors for the facile and real-time detection of copper and iron.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, chestnuts are excellent dietary sources that provide carbohydrates, fiber, starch, fatty acids, minerals (mainly potassium, phosphorus, calcium, and magnesium), and vitamins (B9, C and E) [ 8 , 11 ]. In Europe, the chestnut sector has shown growing interest over recent years, leading to high investments being made from governments, industries, and factories to this sector [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are indications that chestnuts are a rich source of tannins [ 9 , 10 ], most studies have evaluated the use of leaves, bark, and wood [ 8 , 10 , 11 ], and scarce information is available about the potential use of other types of chestnut waste, e.g., chestnut burrs. Studies on chestnut by-products revealed a good profile of bioactive compounds with antioxidant, anticarcinogenic, and cardioprotective properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%